Exploring Juvenile Delinquency: An in-depth Analysis through the Lens of Differential Association Theory - Jasmisari, Mutiara; Sekarningrum, Bintarsih (Jurnal Sosiologi Andalas, 2024)
Abstract: This study delves into the intricate dynamics of adolescent juvenile delinquency by examining the Lens of the Differential Association Theory. Focused on the unique context of adolescents at SMAN 21 Bandung, the study employs qualitative research methods to explore the multifaced relationships between differential association Dynamics and juvenile delinquency. Through in-depth analysis, including comprehensive interviews, observations, and literature reviews, the research sheds light on how adolescents learn and internalize deviant behaviours within their deviant subculture. The findings indicate that deviant behaviour develops a learning process where deviance is perceived as something. Additionally, deviant behaviour is the behaviour of fellow perpetrators in deviant subcultures, establishing an environment in which they feel secure engaging in delinquent activities since there is no one to interfere or report them. The existence of negative interactions serves as a trigger for teenagers to engage in delinquency, highlighting the need for increased supervision from parents and teachers. Furthermore, it is necessary to implement tactics to tackle teenage delinquency within educational institutions, aiming to deter their engagement in deviant behaviours.